SGIP1α, but Not SGIP1, is an Ortholog of FCHo Proteins and Functions as an Endocytic Regulator - Lee, Sang-Eun; Cho, Eunji; Jeong, Soomin; Song, Yejij; Kang, Seokjo; Chang, Sunghoe (Frontiers in Cell and Developmental Biology, 2021)
Src homology 3-domain growth factor receptor-bound 2-like interacting protein 1 (SGIP1), originally known as a regulator of energy homeostasis, was later found to be an ortholog of Fer/Cip4 homology domain-only (FCHo) proteins and to function during endocytosis. SGIP1α is a longer splicing variant in mouse brains that contains additional regions in the membrane phospholipid-binding domain (MP) and C-terminal region, but functional consequences with or without additional regions between SGIP1 and SGIP1α remain elusive. Moreover, many previous studies have either inadvertently used SGIP1 instead of SGIP1α or used the different isoforms with or without additional regions indiscriminately, resulting in further confusion. Here, we report that the additional region in the MP is essential for SGIP1α to deform membrane into tubules and for homo-oligomerization, and SGIP1, which lacks this region, fails to perform these functions. Moreover, only SGIP1α rescued endocytic defects caused by FCHo knock-down. Thus, our results indicate that SGIP1α, but not SGIP1, is the functional ortholog of FCHos, and SGIP1 and SGIP1α are not functionally redundant. These findings suggest that caution should be taken in interpreting SGIP1’s role in endocytosis.